2007
DOI: 10.1513/pats.200707-097th
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-directed Therapy in Acute Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Acute exacerbations of chronic obstructive pulmonary disease (COPD) are important events in the natural history of this chronic lung disorder. These events can be caused by a large number of infectious and noninfectious agents and are associated with an increased local and systemic inflammatory response. Their frequency and severity have been linked to progressive deterioration in lung function and health status. Infectious pathogens ranging from viral to atypical and typical bacteria have been implicated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 170 publications
0
12
0
Order By: Relevance
“…It has been estimated that approximately 40%–50% of AECOPD cases are due to bacterial infections 34. The precise contribution of bacterial infection is difficult to define because the airways of COPD patients may be chronically colonized 3,4. Acquisition of new strains of Haemophilus influenzae and Moraxella catarrhalis, rather than bacterial load, appears to be the most important factor in the pathogenesis of acute exacerbations 35.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that approximately 40%–50% of AECOPD cases are due to bacterial infections 34. The precise contribution of bacterial infection is difficult to define because the airways of COPD patients may be chronically colonized 3,4. Acquisition of new strains of Haemophilus influenzae and Moraxella catarrhalis, rather than bacterial load, appears to be the most important factor in the pathogenesis of acute exacerbations 35.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses support these recommendations to reduce mortality and treatment failures 2. Although purulent sputum and growth of a bacterial pathogen suggest infection, definitive causality with an AECOPD is difficult because patients may be chronically colonized 3,4. In addition, recent studies using molecular diagnostics indicate that a substantial proportion of AECOPD are associated with viral infection 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…Many species of bacteria have been identified in the airways of patients with asthma or COPD (8,9,12,13). However, the role of bacteria in disease acute exacerbations as well as progression remains controversial (14,15). The common bacteria seen in asthma and COPD airways include, but are not limited to, Mycoplasma pneumoniae (Mp), nontypeable Haemophilus influenzae (NTHi), and Moraxella catarrhalis (12,13).…”
mentioning
confidence: 99%
“…The precise contribution of bacterial infection is difficult to define because the airways of COPD patients may be chronically colonized [33,34]. Acquisition of new strains of Haemophilus influenzae and Moraxella catarrhalis, rather than bacterial load, appears to be the most important factor in the pathogenesis of acute exacerbations [35]. This factor has not been accounted for in AECOPD antibiotic trials and might explain the modest beneficial effects of antimicrobial treatments observed.…”
Section: Discussionmentioning
confidence: 99%